1986
DOI: 10.1002/1097-0142(19860415)57:8+<1648::aid-cncr2820571303>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

The preclinical development of roferon®-A

Abstract: Interferon alfa-2a (Roferon-A, Hoffmann-La Roche Inc., Nutley, NJ) is identical to one of approximately 15 subtypes of interferon alpha made by human leukocytes and is produced in bacteria using recombinant DNA techniques. In its antiviral, antiproliferative, and immunomodulatory activities it is similar to leukocyte interferon alpha. These activities are species-restricted and have been demonstrable, thus far, only in humans, certain other primates, bovines, and guinea pigs or cells derived therefrom. The pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
19
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(25 citation statements)
references
References 30 publications
6
19
0
Order By: Relevance
“…However, in contrast to mouse IFN-a, 100 000 IU of human IFN-a (as a control group for mouse IFN-a), a dose which is 10 times that of the mouse IFN-a, had no stimulatory effect on the expression of these IFN-regulated genes (Figure 1), consistent with the species-restricted activity of IFN-a. 32,33 Very similar results were obtained in two other experiments. Moreover, as expected, heat inactivation (1001C for 10 min) completely abolished the stimulatory effect of the IFN-a on IFN-regulated gene expression (data not shown), excluding contamination by endotoxin as a possible causative factor.…”
Section: Resultssupporting
confidence: 80%
“…However, in contrast to mouse IFN-a, 100 000 IU of human IFN-a (as a control group for mouse IFN-a), a dose which is 10 times that of the mouse IFN-a, had no stimulatory effect on the expression of these IFN-regulated genes (Figure 1), consistent with the species-restricted activity of IFN-a. 32,33 Very similar results were obtained in two other experiments. Moreover, as expected, heat inactivation (1001C for 10 min) completely abolished the stimulatory effect of the IFN-a on IFN-regulated gene expression (data not shown), excluding contamination by endotoxin as a possible causative factor.…”
Section: Resultssupporting
confidence: 80%
“…The emergence of anti-Albuferon antibodies was expected on the basis of published reports of IFN-␣ administration in monkeys (Trown et al, 1986). In the study reported here, the development of antibodies in 10 of 12 animals coincided with the observed increase in clearance of Albuferon from the circulation.…”
Section: Discussionsupporting
confidence: 76%
“…The development of antibodies after IFN-␣ injection was expected on the basis of reports by Trown et al (1986) and Bailon et al (2001). Therefore, in this study, serum samples were assessed for the development of anti-Albuferon antibodies using an ELISA method.…”
Section: Immunogenicity Analysismentioning
confidence: 99%
“…The use of IFN-ot alone and in combination with AZT in other mammalian retrovirus infections is limited, but similar to its application for HIV infections, these agents act synergistically to prophylactically prevent murine and feline retrovirus infections (42,51). Phase I studies in humans have indicated a half-life of IFN-oa in plasma of 2 to 3 h following subcutaneous injection, with dose limitations related to pyrexia, lethargy, myalgia, and hematological toxicity (38,48). Initial clinical trials with IFN-cx against HIV-associated Kaposi sarcoma have been encouraging in terms of antiviral and antitumor responses, significant increases in CD4+ cells, and decreases in circulating viral antigen in those patients who respond to therapy (4,10,23).…”
mentioning
confidence: 99%